2022
DOI: 10.1590/s1984-29612022031
|View full text |Cite
|
Sign up to set email alerts
|

Helminth community structure of Didelphis marsupialis (Didelphimorphia, Didelphidae) in a transition area between the Brazilian Amazon and the Cerrado

Abstract: Although the common opossum, Didelphis marsupialis (Didelphimorphia: Didelphidae) is a species widely distributed in South America, knowledge about their helminth parasites and helminth community structure is scarce. The aims of this study were to describe the species composition and analyze the structure of the helminth community of the common opossum in an area of the Amazonian Arc in northern Mato Grosso. The helminths were recovered, counted, and identified in 32 individuals. Overall, 10,198 specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…In studies carried out with didelphids, this relationship between host body size and helminth abundance has already been demonstrated, postulating that larger and older hosts have more parasites than young hosts (Cirino et al 2020;Freitas et al 2022) because they may acquire parasites during their lifetime.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In studies carried out with didelphids, this relationship between host body size and helminth abundance has already been demonstrated, postulating that larger and older hosts have more parasites than young hosts (Cirino et al 2020;Freitas et al 2022) because they may acquire parasites during their lifetime.…”
Section: Discussionmentioning
confidence: 81%
“…Studies of the helminth fauna or helminth community structure of small didelphids are scarce. Most of them were carried out for large marsupials, such as Didelphis marsupialis (Freitas et al 2022), Didelphis aurita (Costa-Neto et al 2019), Didelphis albiventris (Cirino et al 2022), Metachirus myosurus (Cirino et al 2020) and Philander opossum (Ramírez-Cañas et al 2019). For the genus Marmosa, there is only one study comparing the helminth structure of two sympatric species of this genus (M. demerarae and M. murina) in French Guiana (Byles et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding host body size, male host body size was an important variable for the abundance of helminth species. In studies carried out with didelphids, this relationship between host body size and helminth abundance has already been demonstrated, postulating that larger and older hosts have more parasites than young hosts (Cirino et al 2020; Freitas et al 2022) because they may acquire parasites during their lifetime.…”
Section: Discussionmentioning
confidence: 85%
“…The study of the helminth fauna of D. marsupialis , which was carried out in the same locality as the present study, reported the same helminth species richness observed for M. constantiae (nine species). However, D. marsupialis and M. constantiae shared only two species, A. raillieti and O. microcephalus, which have been registered in several didelphids (Varella et al 2022; Freitas et al 2022). Jiménez et al (2011) reported 10 helminth species for the marsupial Philander opossum in French Guiana and 12 in Mexico, among which A. raillieti and O. microcephalus were the only species in common with the present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation